High Step-Up DC-DC Converter Using Switching Cells for PV Applications - Nguyen, Dinh Tuyen; Duong, Truong Khang (Journal of Technical Education Science, 2025)
In the context of a rapidly evolving global energy landscape transitioning towards renewable energy sources, the need for innovative, efficient, and flexible power conversion technologies has become increasingly critical. This paper presents a high step-up DC-DC converter using switching cells with a single switch for photovoltaic (PV) applications. The proposed topology features a simplified structure with only one switch, combining switched cells with inductors and capacitors. This feature helps to reduce the current stress through the inductor and the voltage stress on the capacitor. This design achieves high step-up conversion with a small duty cycle while maintaining simplicity in control and low voltage stress on the semiconductor devices. These attributes contribute to an overall improvement in the converter’s efficiency. The paper provides a comprehensive analysis in continuous conduction mode (CCM) and details the design of components, emphasizing the practicality and feasibility of the proposed topology. The operation of the proposed converter is validated through comprehensive 200-W/20-kHz simulation results, carried out using PSIM software.